2008
DOI: 10.1016/j.molimm.2008.08.278
|View full text |Cite
|
Sign up to set email alerts
|

Btk regulates localization, in vivo activation, and class switching of anti-DNA B cells

Abstract: The autoimmune disease systemic lupus erythematosus (SLE) is characterized by loss of tolerance to nuclear antigens such as chromatin, DNA, and RNA. This focused autoreactivity is thought to arise from the ability of DNA or RNA specific B cells to receive dual signals from the BCR and TLR9 or TLR7, respectively. The Tec kinase Btk is necessary for the production of anti-DNA antibodies in several murine models of SLE. To assess the role of Btk in the fate of DNA reactive B cells, we generated Btk−/− mice carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 53 publications
7
33
0
Order By: Relevance
“…Finally, we showed that all 3 TKIs suppress Btk activity in memory B-cell subsets, known to be critical to B-cell memory development and class switching. 48 Our study was not designed to address the underlying reasons for differential responses to pneumococcal vaccine in CML patients on TKI. A possible explanation could be variations in serum TKI levels due to interindividual differences in drug metabolism 49 or adherence that may in turn impact the in vivo B-cell response to the vaccine.…”
Section: Tkis Impair B-cell Immune Response In CML 235mentioning
confidence: 99%
“…Finally, we showed that all 3 TKIs suppress Btk activity in memory B-cell subsets, known to be critical to B-cell memory development and class switching. 48 Our study was not designed to address the underlying reasons for differential responses to pneumococcal vaccine in CML patients on TKI. A possible explanation could be variations in serum TKI levels due to interindividual differences in drug metabolism 49 or adherence that may in turn impact the in vivo B-cell response to the vaccine.…”
Section: Tkis Impair B-cell Immune Response In CML 235mentioning
confidence: 99%
“…Re-introduction of Btk expression at low levels (Btk lo ) in the B6.56R mice restored anti-DNA IgM but not anti-DNA IgG. Overexpression of Btk had no effect on anti-dsDNA IgG levels in B6.56R mice [15]. …”
Section: Bruton’s Tyrosine Kinasementioning
confidence: 99%
“…Myeloid cells, B cells [149][150][151][152][153] CD303 (BDCA-2) Plasmacytoid dendritic cells [154] Epo: Erythropoietin; GPVI: Collagen receptor glycoprotein VI; R: Receptor; TLR: Toll like receptor; TRAIL: TNF-related apoptosis-inducing ligand.…”
Section: Pre-bcrmentioning
confidence: 99%